Evaluación de la calidad del agua y diseño de un sistema alternativo de tratamiento, en el valle acuícola Quillán, Tungurahua – Ecuador, 2021 - Llugsha Moreta, Nataly Marisol (2021)
Rainbow trout aquaculture contributes progressively to the quality of life in rural communities. When aquatic habitat conditions are inadequate, the yield of the species decreases and the quality of the water resource is degraded. The present research was carried out at the Aquaculture Research Center "El Descanso" (CIA-ED), in the Quillán Valley, where the water quality was evaluated, pre and post aquaculture use for 30 days, in order to design an alternative treatment system for the optimization of certain characteristics, at the catchment point of the tributary to the center. For this purpose, the following parameters were sampled in the influent and effluent: phosphates, nitrates, nitrites, hydrogen potential, dissolved oxygen, ambient and water temperature, for 30 days; additionally, a laboratory analysis was performed for the following parameters: fecal coliforms, biochemical oxygen demand, and after considering the geogenic origin of the water, an arsenic test was performed. Based on the parameters, the water quality was determined using the Objective Water Quality Index (ICAOBJ), which was established at the Universidad Santiago de Chile, also, a classification was made according to table two and table nine of the Ministerial Agreement 097-A of Ecuador. The ICAOBJ determined that the water quality at the point of entry is medium and, according to Ministerial Agreement 097-A, it is not suitable for the preservation of aquatic life in freshwater; also, in the effluent, the ICAOBJ determined that the water quality is very low; however, the classification in table nine of the permissible limits for discharge into a freshwater body determined that most of them are below the standards. Therefore, reducing the pollutants present in the water is necessary to increase the productive yield of aquatic species and indispensable to preserve water resources. Following the above, the alternative treatment system proposed in this research was designed to optimize the following characteristics of the influent: fecal coliforms, nitrates, phosphates and dissolved oxygen, it consists of a tank 4.5 meters long, 3m. It consists of a tank 4.5 meters long, 3m. wide, 2m. high, distributed in three levels and within the same, phases of screening, adsorption, ozonation, oxygenation and phytoremediation were integrated by means of: grids, desander, ozone generator, aeration pump, Achira artificial floating islands and a base composed of ground corn stover. This is an alternative adapted to certain parameters, essential in rainbow trout farming, and which, at the same time, would allow reducing the pollutant load of the effluent, by means of low-cost materials and equipment, making it economically and environmentally viable.